Stability of Heat and Energy Characteristics of Refrigerating Units as a Condition of Quality Increase of Agricultural Production Storage - E. Bashniak , Sergey; A. Ladygin, Evgeniy; S. Anisimova, Olga; Yu. Kontareva, Valentina; G. Papchenko, Natalya; M. Bashniak, Irina (KnE Life Sciences, 2021)
This article provides information about the importance of stable thermal operating modes of refrigeration machines in the condition of changes in the thermal load on the compressor. We also consider the problem of the minimum energy consumption of refrigeration machines. These two parameters characterize the storage quality of agricultural products in refrigeration machines. It is shown that the temperature stability of the cooling chambers and the minimum energy consumption of the cooling process determine the refrigerator efficiency and, ultimately, the production cost. The article proposes continuous monitoring of the heat and energy indicators of refrigerators. These indicators are recorded and after the set period of operation, control and verification measurements of the control refrigeration machine’s heat and energy indicators are performed. The convergence or divergence of these indicators is used to evaluate the stability of the cooling chambers’ temperature regimes and the specific energy consumption. We also consider the influence of time on the performance of the compression refrigeration machine changes and methods of current technical condition diagnostics. If the deviations are insignificant, the program goes through the cycle to the beginning of monitoring and after a set period of time again automatically performs control measurements and evaluation of deviations. In the case of significant deviations, the decision-making subroutine is activated: either to operate the refrigerator further; perform its maintenance; suspend its operation; or replace it. Keywords: refrigeration units, cooling, heat and power characteristics, management controller, storage quality of agricultural production